Altered Spontaneous Regional Brain Activity in the Insula and Visual Areas of Professional Traditional Chinese Pingju Opera Actors - Zhang, Weitao; Zhao, Fangshi; Qin, Wen; Ma, Lin (Frontiers in Neuroscience, 2018)
Recent resting-state fMRI studies have revealed neuroplastic alterations after long-term training. However, the neuroplastic alterations in professional traditional Chinese Pingju opera actors remain unclear. Twenty professional traditional Chinese Pingju opera actors and 20 age-, sex-, and handedness-matched laymen were recruited. Resting-state fMRI was obtained by using an echo-planar imaging sequence, and two metrics, amplitude of low frequency fluctuation (ALFF) and regional homogeneity (ReHo), were utilized to assess spontaneous neural activity during resting state. Professional traditional Chinese Pingju actors exhibited significantly decreased ALFF in the bilateral calcarine gyrus and cuneus, decreased ReHo in the bilateral superior occipital and calcarine gyri, cuneus, and right middle occipital gyrus, and increased ReHo in the left anterior insula compared with laymen. No significant association was found between the spontaneous neural activity and the duration of opera training. The altered spontaneous brain activity in professional traditional Chinese Pingju opera actors may indicate their superior performance in multidimensional professional skills, such as music and face perception, dancing and emotion representation.